Shock propagation in the banking system with real economy feedback - Andras Borsos; Bence Mero (Magyar Nemzeti Bank, 2020)
In this paper we develop a model of shock propagation in the banking system with feedback channels towards the real economy. Our framework incorporates the interactions between the network of banks (exhibiting contagion mechanisms among them) and the network of firms (transmitting shocks to each other along the supply chain) which systems are linked together via loan-contracts. Our hypothesis was, that the feedback mechanisms in these coupled networks could amplify the losses in the economy beyond the shortfalls expected when we consider the subsystems in isolation. As a test for this, we embedded the model into a liquidity stress testing framework of the Central Bank of Hungary, and our results proved the importance of the real economy feedback channel, which almost doubled the system-wide losses. To illustrate the versatility of our modeling framework, we presented two further applications for different policy purposes: (i) We elaborated a way to use the model for SIFI identification, (ii) and we showed an example of assessing the impact of shocks originated in the real economy.
Keywords: G01; G21; G28; C63; 330; systemic risk; financial network; production network; contagion